Asesmen Psikologis sebagai Alat Bantu Konselor: Mengungkap Potensi dan Permasalahan Konseli - Yulianto, Afifah Nauffatih (Lembaga Yasin AlSys, 2025)
Psychological assessment plays a strategic role in guidance and counseling practice, serving as a means to obtain a comprehensive understanding of the counselee’s potential, psychological condition, and personal challenges. This study aims to examine the functions and contributions of psychological assessment in supporting the effectiveness of the counseling process. A descriptive-analytical approach is employed to explore the role of assessment in objectively understanding individual characteristics across cognitive, affective, social, and academic dimensions. The assessment instruments utilized include test techniques, such as achievement, interest, aptitude, and personality tests as well as non-test techniques such as interviews, observations, questionnaires, and problem checklists. The combination of these approaches provides an accurate informational foundation for designing targeted intervention strategies aligned with the actual needs of the counselee. Beyond serving as an initial diagnostic tool, assessment outcomes also serve as a crucial reference for ongoing evaluation of the counseling process. Thus, psychological assessment is not merely an administrative procedure but an integral part of professional counseling that supports the optimization of individual potential and the reflective, well-being-oriented resolution of personal issues.